Theoretical Foundations of Pastoral Care in Christian Tradition - Zuhal Agılkaya-Sahin (Spiritual Psychology and Counseling, 2016)
The growing academic and institutional interest in pastoral care and counseling raises attention day by day. However there is no institutionally established concept and practice of pastoral care in Turkey’s prevalent Islamic tradition. Therefore there is a lack of theoretical foundation for this service that wants to be developed and established in Turkey. In fact pastoral care services are quite well developed in Christian tradition. Especially in Germany pastoral care and counseling has a deep-rooted history and professional practice. Thus in this paper in order to give an insight into theoretical foundations of German pastoral care and counseling the concept is illustrated in terms of definition, characteristics, subjects, objects, aims, tasks and theology.